Beneficial intervertebral disc and muscle adaptations in high-volume road cyclists - Belavy, D. L.; Quittner, M.; Ridgers, N. D.; Ling, Y.; Connell, D.; Trudel, G.; Rantalainen, T. (Medicine & Science in Sports & Exercise, 2019)
PURPOSE: Cycling is widely practiced as a mode of transportation, a leisurely pursuit, and a competitive sport. Approximately half of cyclists experience low back pain. Yet, there has been limited study of spine tissue adaptations due to cycling.